Unexplained anasarca in type 1 diabetes mellitus: Breaking the hypoalbuminemia - Persistent diarrhea cycle - Varuna Vyas; Daisy Khera; Aliza Mittal; Kuldeep Singh (Wolters Kluwer Medknow Publications, 2022)
Background: Undiagnosed Type 1 diabetes mellitus (T1DM) often presents as diabetic ketoacidosis (DKA). We report a child with newly diagnosed T1DM who developed anasarca and persistent diarrhea following resolution of DKA and was referred to us for the same. Clinical Description: We reviewed the clinical history, examination, and investigations that had been undertaken. Our clinical evaluation was in concurrence with the referring hospital-anasarca with probable partially treated spontaneous bacterial peritonitis (SBP). However, the cause of the subacute anasarca and persistent diarrhea was unclear. The child was empirically started on broad-spectrum antibiotics for the SBP, a high-protein diet to build up the protein, and continued the same subcutaneous insulin, on which he was euglycemic. After ruling out usual causes, i.e., renal, hepatic, and cardiac, we reviewed the possibility of celiac disease, tuberculosis, insulin edema, and hypothyroidism. Management: When he did not improve despite a good appetite, adherence to management, and all tests were inconclusive, we reviewed the etiopathogenesis. Untreated T1DM had led to chronic negative catabolism that had precipitated severe hypoproteinemia. A vicious cycle had set in which hypoalbuminemia was leading to bowel wall edema, resulting in protein malabsorption, perpetuation of diarrhea, and further hypoproteinemia. Our assumption proved to be correct when a single dose of parenteral albumin broke the cycle, and the child improved drastically with the resolution of diarrhea within 24 h and the edema in a few days. Conclusions: This case highlights the implications of severe catabolism in a patient with untreated diabetes and how this may be a self-perpetuating condition.